The use of PHC clinic-based women's groups for financial empowerment in a rural area - LR Uys; BR Bhengu; B Majumdar (AOSIS, 2006)
The article is based on a four-year project during which Primary Health Care (PHC) nurses worked with women's groups in their areas. The aim of the study was to explore the involvement of PHC nurses in economic empowerment, both in terms of health promotion and in terms of the PHC approach. In particular the objectives were to establish whether nurses could lead economic empowerment groups, whether such groups could establish adequate external links and become financially viable. Eleven groups were used as case studies, and a cross-case analysis was done in terms of the three objectives. It was found that between the women and the nurses, adequate leadership existed for the groups to function well. Very limited external linkages were established, notwithstanding efforts in this regard. Nine out of 11 groups contributed to financial welfare of their members after 18 months, but a range of problems with regard to financial viability are identified.